1984
DOI: 10.1063/1.446990
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic circular dichroism studies of matrix-isolated atoms: Excited state spin-orbit coupling constant reduction of copper in the noble gases

Abstract: The absorption and magnetic circular dichroism spectra of the 2P+-2S transition of matrixisolated copper atoms have been measured in krypton and xenon matrices. A dramatic reversal in the MCD 'if' term pattern is observed. From a spectral band moment analysis it is shown that: (1) noncubic lattice cage vibrational motions are more important than cubic ones in contributing to the observed bandwidths and (2) the Cu excited state spin-orbit coupling constant (A) in krypton is reduced to 57% of its gas phase value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…Due to their large spectral widths, the individual components of the triplet structures strongly overlap and peak positions reported in different publications vary considerably. Triplet structures of the nS → nP transitions have also been observed in absorption spectra of matrix-isolated noble metal atoms [273][274][275][276][277][278]. In those systems usually a single (substitution) trapping site is observed.…”
Section: Optical Absorptionmentioning
confidence: 75%
See 2 more Smart Citations
“…Due to their large spectral widths, the individual components of the triplet structures strongly overlap and peak positions reported in different publications vary considerably. Triplet structures of the nS → nP transitions have also been observed in absorption spectra of matrix-isolated noble metal atoms [273][274][275][276][277][278]. In those systems usually a single (substitution) trapping site is observed.…”
Section: Optical Absorptionmentioning
confidence: 75%
“…The phenomenon is well known in matrix-isolation spectroscopy as Jahn-Teller effect. As discussed in [282,276,267] the main contribution comes from tetragonal stretching and bending (e g ) modes, and a smaller contribution from trigonal (t 2g ) modes. Calculations of Jahn-Teller spectra were presented for K in solid Ar [265], for Li in Ar, Kr, and Xe [266,285], and for Na in Xe [267].…”
Section: Optical Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the early 1970's the visible, ultraviolet and other spectra of atoms trapped in noble-gas matrices have been reported by many authors. [1][2][3][4][5][6][7][8][9][10][11][12][13][14]16 The Cu atom in a Ne matrix is of interest, because four 12,14 distinct line shapes were observed, not merely three, 11 as set out in Table 1. Three Cu line shapes (known as a triplet 12 ) were also observed in other noble matrices of Ar, Kr, and Xe, [2][3][4][5][6][7][8][9][10] and these are believed to originate from the Cu 4s 1 2 S -4p 1 2 P transition.…”
Section: Introductionmentioning
confidence: 99%
“…Several absorption studies [1] of matrix-isolated metal atoms have indicated pronounced threefold splitting on resonance P ← S transitions and while magnetic circular dichroism (MCD) work [2,3] has revealed the origins of the characteristic threefold splitting is likely due to JahnTeller coupling in the excited P state, a fundamental obstacle precluding a conclusive assignment is lack of knowledge of the site occupied by the guest atom in the host solid. Clearly, a better understanding of the underlying physical effects contributing to the spectral behavior of these model matrix-isolated systems relies on an identification of guest site occupancy.…”
Section: Introductionmentioning
confidence: 99%